Dietary and Microbial Metabolites in the Regulation of Host Immunity - Shibata, Naoko; Kunisawa, Jun; Kiyono, Hiroshi (Frontiers in Microbiology, 2017)
Mucosal surfaces in the body, especially the intestine, are constantly exposed to trillions of microbiomes. Accumulating evidence has revealed that changes in the composition of the gut microbiome, especially that of the commensal bacteria population, are frequently associated with immunologic disorders. These changes coincide with changes in the production of certain dietary metabolites. Recent studies have uncovered the molecular and cellular mechanisms underlying the relationships among diet, commensal bacteria, and the host immune system. In this review, we describe how dietary and microbial metabolites modulate host immunity.